Respostas

2013-06-11T16:57:49-03:00

x= -b +/= raiz de b  ao quadrado - 4ac

                           2a

5 +/- 25 - 4.1.6  /  2 >>  5+/- raiz de> 25 - 24  /  2 >>  

 

x = 5 +/- raiz de 1 /  2   >>   x = 5 +- 1 / 2

 

x linha = 5 + 1 / 2 = 3      

 

x duas linhas = 5 - 1 / 2 = 2

1 1 1
2013-06-11T17:13:09-03:00

x²-5x+6

Δ= b²-4.a.c

Δ= (-5)²-4.1.6

Δ= 25-24

Δ= 1

 

-b ± √Δ

      2.a

-(-5) ± √1

      2.1

5 ± 1

    2

x' = 5+1= 6 = 3

        2      2

x'' = 5-1 = 4 = 2

         2       2

1 5 1